2018
DOI: 10.1038/s41598-018-22246-4
|View full text |Cite
|
Sign up to set email alerts
|

Marker-assisted introgression of three dominant blast resistance genes into an aromatic rice cultivar Mushk Budji

Abstract: Modern high yielding rice varieties have replaced most of the traditional cultivars in recent past. Mushk Budji, is one such short grained landrace known for its aroma and exquisite quality, however, is highly susceptible to blast disease that has led to considerable decline in its area. Mushk Budji was crossed to a triple-gene donor line, DHMAS 70Q 164-1b and followed through marker-assisted foreground and background selection in first and second backcross generations that helped to incorporate blast resistan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 50 publications
3
41
0
Order By: Relevance
“…Till now, more than 100 distinctive blast resistance genes have been identified [14] and out of them, 21 genes have been cloned [15]. Two dominant resistance genes (Pi54 and Pi1) are known to confer resistance against the major virulent races of the pathogen in India and widely used by different research groups [16]. Enormous genetic diversity exists among the BB and blast pathogens across the geographical regions [17], and previous studies indicate that cultivars with a single resistance gene do not provide broad-spectrum resistance [1].…”
Section: Introductionmentioning
confidence: 99%
“…Till now, more than 100 distinctive blast resistance genes have been identified [14] and out of them, 21 genes have been cloned [15]. Two dominant resistance genes (Pi54 and Pi1) are known to confer resistance against the major virulent races of the pathogen in India and widely used by different research groups [16]. Enormous genetic diversity exists among the BB and blast pathogens across the geographical regions [17], and previous studies indicate that cultivars with a single resistance gene do not provide broad-spectrum resistance [1].…”
Section: Introductionmentioning
confidence: 99%
“…Enhancing the host rice resistance is being considered as the best approach to handle the rice blast disease. Pyramiding of broad-spectrum R genes into a rice variety has been proved to be an effective way to control rice blast (Ashkani et al 2015; Khan et al 2018). Ellur et al (2016) introduced Pi2 and Pi54 into Basmati rice simultaneously, and found that the PPLs with Pi2 and Pi54 were not only effective in northern and eastern parts of India, but also in the southern parts of the country such as Pattambi, Kerala, and Gudalur, Tamil Nadu.…”
Section: Discussionmentioning
confidence: 99%
“…However, which R gene pyramiding patterns show broad-spectrum and stable blast resistance is still little known. The resistance effects of PPLs with different broad-spectrum resistance genes, such as Pi2 / Pi1 , Piz-t / Pi54 and Pi1 / Pi54 could be significantly improved as compared to the monogenic lines with single R gene (Jiang et al 2012; Khan et al 2018; Xiao et al 2017). However, gene pyramiding does not always mean that the resistance spectrum could be improved.…”
Section: Introductionmentioning
confidence: 99%
“…R-gene pyramids improve resistance to diverse pathogen isolates [85][86][87][88]. A comprehensive survey of a series of gene pyramids Crop Breed Genet Genom.…”
Section: Gene Pyramiding For Sustainable Control Of Blastmentioning
confidence: 99%